Distinct and nonoverlapping roles for pRB and cyclin D:cyclin-dependent kinases 4/6 activity in melanocyte survival - Yu, Benjamin D. (National Academy of Sciences, 2003)
Deregulation of the p16(INK4a)–cyclin D:cyclin-dependent kinases (cdk) 4/6 –retinoblastoma (pRB) pathway is a common paradigm in the oncogenic transformation of human cells and suggests that this pathway functions linearly in malignant transformation. However, it is not understood why p16(INK4a) and cyclin D:cdk4/6 mutations are disproportionately more common than the rare genetic event of RB inactivation in human malignancies such as melanoma. To better understand how these complexes contribute to altered tissue homeostasis, we blocked cdk4/6 activation and acutely inactivated Rb by conditional mutagenesis during mouse hair follicle cycling. Inhibition of cdk4/6 in the skin by subcutaneous administration of a membrane-transducible TAT-p16(INK4a) protein completely blocked hair follicle growth and differentiation. In contrast, acute disruption of Rb in the skin of homozygous Rb(LoxP/LoxP) mice via subcutaneous administration of TAT-Cre recombinase failed to affect hair growth. However, loss of Rb resulted in severe depigmentation of hair follicles. Further analysis of follicular melanocytes in vivo and in primary cell culture demonstrated that pRB plays a cell-autonomous role in melanocyte survival. Moreover, functional inactivation of all three Rb family members (Rb, p107, and p130) in primary melanocytes by treatment with a transducible TAT-E1A protein did not rescue the apoptotic phenotype. These findings suggest that deregulated cyclin D:cdk4/6 complexes and pRB perform nonoverlapping functions in vivo and provide a cellular mechanism that accounts for the low incidence of RB inactivation in cancers such as melanoma.